A bimetallic synergistic effect on the atomic scale of defect-enriched NiV-layered double hydroxide nanosheets for electrochemical phenol hydroxylation. Issue 12 (23rd February 2022) - Li, Guangyao; Xu, Yanqi; Pan, Hong; Xie, Xiangli; Chen, Rongrong; Wu, Di; Wang, Linjiang
Abstract : Defect-enriched NiV-LDH-NS with a bimetallic synergistic effect were prepared by a one-step co-precipitation strategy and the electron-rich defects accelerated the formation of hydroxyl radicals (˙OH) to participate in the phenol hydroxylation. Abstract : Vanadium-based catalysts have long been applied in arene Csp 2 –H bond activation and functionalization, but enormous challenges remain in terms of high activity, selectivity, and stability. Herein, defect-enriched NiV-layered double hydroxide nanosheets (NiV-LDH-NS) with a bimetallic synergistic effect were prepared by a one-step co-precipitation strategy as an electrocatalyst for phenol hydroxylation. The appropriate valence band of NiV-LDH-NS could provide a suitable thermodynamic driving force in electrochemical phenol hydroxylation and simultaneously avoid overoxidation. X-ray absorption fine spectroscopy (XAFS) revealed a defect-enriched structure (VNi and VO ) and low coordination structure (Ni–O and V–O) in NiV-LDH-NS. X-ray absorption spectroscopy (XAS) and electrochemical characterization showed that these higher energy states within Ni and V resulted in intense electronic interactions and fast electron transfer in NiV-LDH-NS; meanwhile, the electron-rich defects accelerated the V 4+ /V 5+ redox, generating hydroxyl radicals (˙OH) to participate in the electrochemical phenol hydroxylation. Analysis by high performance liquid chromatography (HPLC), gas chromatography-mass spectrometry (GC-MS), and 1 H nuclear magnetic resonance ( 1 H NMR) further confirmed the existence of target product hydroquinone (HQ), which was optimally achieved with a 72.2% conversion of phenol and a 71.6% selectivity of HQ.